EULAR definition of arthralgia suspicious for progression to rheumatoid arthritis. Issue 3 (6th October 2016) - van Steenbergen, Hanna W; Aletaha, Daniel; Beaart-van de Voorde, Liesbeth J J; Brouwer, Elisabeth; Codreanu, Catalin; Combe, Bernard; Fonseca, João E; Hetland, Merete L; Humby, Frances; Kvien, Tore K; Niedermann, Karin; Nuño, Laura; et al.
Abstract : Background: During the transition to rheumatoid arthritis (RA) many patients pass through a phase characterised by the presence of symptoms without clinically apparent synovitis. These symptoms are not well-characterised. This taskforce aimed to define the clinical characteristics of patients with arthralgia who are considered at risk for RA by experts based on their clinical experience. Methods: The taskforce consisted of 18 rheumatologists, 1 methodologist, 2 patients, 3 health professionals and 1 research fellow. The process had three phases. In phase I, a list of parameters considered characteristic for clinically suspect arthralgia (CSA) was derived; the most important parameters were selected by a three-phased Delphi approach. In phase II, the experts evaluated 50 existing patients on paper, classified them as CSA/no-CSA and indicated their level of confidence. A provisional set of parameters was derived. This was studied for validation in phase III, where all rheumatologists collected patients with and without CSA from their outpatient clinics. Results: The comprehensive list consisted of 55 parameters, of which 16 were considered most important. A multivariable model based on the data from phase II identified seven relevant parameters: symptom duration <1 year, symptoms of metacarpophalangeal (MCP) joints, morning stiffness duration ≥60 min, most severe symptoms in early morning, first-degree relative with RA, difficulty with making a fist and positive squeeze test of MCP joints. In phase III, the combination of these parameters was accurate in identifying patients with arthralgia who were considered at risk of developing RA (area under the receiver operating characteristic curve 0.92, 95% CI 0.87 to 0.96). Test characteristics for different cut-off points were determined. Conclusions: A set of clinical characteristics for patients with arthralgia who are at risk of progression to RA was established.